ON A LINEARIZED COVERINGS OF A CUBIC HOMOGENEOUS EQUATION OVER A FINITE FIELD. UPPER BOUNDS - Gabrielyan, V.P. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
We obtain upper bounds of the complexity of linearized coverings for some special solutions of the equation x_1x_2x_3 + x_2x_3x_4 + … + x_3nx_1x_2 + x_1x_3x_5 + x_4x_6x_8 + … + x_3n-2x_3nx_2 = b over an arbitrary finite field.